Optimization of Nonambulant Mass Casualty Decontamination Protocols as Part of an Initial or Specialist Operational Response to Chemical Incidents. (2nd January 2019) - Chilcott, Robert P.; Mitchell, Hannah; Matar, Hazem
Abstract: Objective : The UK's Initial Operational Response (IOR) is a new process for improving the survival of multiple casualties following a chemical, biological, radiological or nuclear incident. Whilst the introduction of IOR represents a patient-focused response for ambulant casualties, there is currently no provision for disrobe and dry decontamination of nonambulant casualties. Moreover, the current specialist operational response (SOR) protocol for nonambulant casualty decontamination (also referred to as "clinical decontamination") has not been subject to rigorous evaluation or development. Therefore, the aim of this study was to confirm the effectiveness of putatively optimized dry (IOR) and wet (SOR) protocols for nonambulant decontamination in human volunteers.Methods : Dry and wet decontamination protocols were objectively evaluated using human volunteers. Decontamination effectiveness was quantified by liquid chromatography–mass spectrometry analysis of the recovery of a chemical warfare agent simulant (methylsalicylate) from skin and hair of volunteers, with whole-body fluorescence imaging to quantify the skin distribution of residual simulant.Results : Both the dry and wet decontamination processes were rapid (3 and 4 min, respectively) and were effective in removing simulant from the hair and skin of volunteers, with no observable adverse effects related to skin surface spreading of contaminant.Conclusions : Further studies are required to assess the combined effectiveness of dry and wet decontamination under more realistic conditions and to develop appropriate operational procedures that ensure the safety of first responders.